Understanding Digital Zakat Behavior through Innovation Resistance, Self-Efficacy, and Religious Orientation - Rejeki, Dyah Arum Sri; Aligarh, Frank (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the factors influencing behavioral intention and actual usage of digital zakat in Indonesia. The research integrates the Theory of Planned Behavior with the Innovation Resistance Theory and adds self-efficacy and religious orientation as additional variables. A quantitative approach was applied through an online survey analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that attitude, subjective norms, perceived behavioral control, self-efficacy, and religious orientation positively affect the intention to use digital zakat, while innovation resistance has a negative effect. Behavioral intention also significantly influences actual usage. This study contributes to Islamic economic literature by highlighting the importance of inclusive, educational, and faith-based strategies for optimizing zakat digitization.